Pedagogy of the Spirit Comparing Evangelical and Latter-day Saint Youth Self-Reported In-Class Spiritual Experiences - Wong, Arch Chee Keen; Gardner, Ryan S.; Sweat, Anthony R. (2017)
This study statistically analyzes data from 756 evangelical and Latter-day Saint youth regarding their perceived in-class spiritual experiences of twenty items related to Christian theology. The data indicates similar spiritual outcomes between the two groups, with no statistically significant differences between eleven of the twenty spiritual experience items. However, evangelical participants most highly reported affective spiritual outcomes and least commonly reported action-oriented spiritual outcomes, while Latter-day Saint youth most highly reported action-oriented spiritual outcomes and least commonly reported cognitive spiritual outcomes. Action-oriented spiritual outcomes constitute the greatest difference between the two groups. We explore how the differences between evangelical and Latter-day Saint pedagogy and theology might account for these differences.